2007
DOI: 10.1097/wnr.0b013e3282efa065
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic removal of hyaluronan affects routing of axons in the mouse optic chiasm

Abstract: Perturbations of interaction of hyaluronan (HA) with its receptor CD44 cause multiple errors in axon routing at the mouse optic chiasm. To investigate this interaction further on the chiasm routing, we studied the axon routing after enzymatic removal of HA from slice preparations of the optic pathway. Hyaluronidase treatment produced an obvious reduction in midline crossing of the first generated axons in E13 chiasms, but had no influence on routing ofthe uncrossed axons in E15 and E16 slices. These findings s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…‘Axonal coats’ of aggrecan are also present in various human basal ganglia regions60, in the human lateral geniculate body61, and in the rat thalamus62, often independently of perineuronal nets. Interestingly, there is evidence that hyaluronan can control axonal outgrowth of optic tract and locus ceruleus neurons636465. Further, removal of hyaluronan promotes regeneration of severed axons in the rat brain66, although addition of low molecular weight hyaluronan oligosaccharides enhances axonal regrowth following spinal cord injury67.…”
Section: Discussionmentioning
confidence: 99%
“…‘Axonal coats’ of aggrecan are also present in various human basal ganglia regions60, in the human lateral geniculate body61, and in the rat thalamus62, often independently of perineuronal nets. Interestingly, there is evidence that hyaluronan can control axonal outgrowth of optic tract and locus ceruleus neurons636465. Further, removal of hyaluronan promotes regeneration of severed axons in the rat brain66, although addition of low molecular weight hyaluronan oligosaccharides enhances axonal regrowth following spinal cord injury67.…”
Section: Discussionmentioning
confidence: 99%
“…In the tissue engineering field, HA has been utilized to repair defects of the skin or of the musculoskeletal system, including cartilage, bone, ligament, and intervertebral discs [28][29][30][31][32][33]. To decrease it's in vitro and in vivo degradation rates, HA usually undergoes chemical modification before being used in tissue engineering [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…These proteoglycans include sulphated molecules chondroitin sulphate proteoglycans (CS-PGs) and heparan sulfate proteoglycans (HS-PGs), a type of nonsulfated linear glycosaminoglycan hyaluronan (HA), and the cell surface carbohydrate molecule SSEA-1, which is also known as CD15 (leukocyte cluster of differentiation 15) and Lewis-x, a member of the Lewis blood group antigens in humans [24]. By immunohistochemisty using antibodies specific for different glycan epitopes and antibodies against carrier proteins of glycans, they observed specific expression of each of these proteoglycans along the retinofugal pathway [11,13,14,17,19,20,22]. They found that cell adhesion molecules that may recognize these proteoglycans [25,26], including L1, the poly-sialylated form of NCAM (PSA-NCAM) and CD44, are also expressed in a site-specific pattern along the optic pathway at comparable developmental stages [15,16], consistent with the previous reports [27,28].…”
Section: Guidance Of Retinal Axons In the Optic Chiasm By Proteoglycansmentioning
confidence: 97%
“…The potential contributions of glycan molecules present in developing brain tissues have long been overlooked. Chan SunOn and colleagues [10][11][12][13][14][15][16][17][18][19][20][21][22][23] explored the potential role of a group of proteoglycans expressed in the ventral diencephalon and in retina, in the routing and organization of optic fibers at the chiasm. These proteoglycans include sulphated molecules chondroitin sulphate proteoglycans (CS-PGs) and heparan sulfate proteoglycans (HS-PGs), a type of nonsulfated linear glycosaminoglycan hyaluronan (HA), and the cell surface carbohydrate molecule SSEA-1, which is also known as CD15 (leukocyte cluster of differentiation 15) and Lewis-x, a member of the Lewis blood group antigens in humans [24].…”
Section: Guidance Of Retinal Axons In the Optic Chiasm By Proteoglycansmentioning
confidence: 99%
See 1 more Smart Citation